Cavernous sinus-orbital apex aspergillus infection in a diabetic patient: A case report. Issue 13 (March 2019) - Huang, Yuanyuan; Gui, Li
Abstract: Rationale: Cavernous sinus-orbital apex aspergillosis is a rare but serious complication of rhinosinusitis. Pathology results are scarce, and this condition is difficult to diagnose based on clinical and radiological results. Patient concerns: A 64-year-old woman presented with cavernous sinus-orbital apex syndrome. Axial and sagittal T1 contrast-enhanced magnetic resonance imaging (MRI) showed a right orbital apex mass abutting the right posterior ethmoid sinus, sphenoid sinus, and cavernous sinus. Diagnosis: Cavernous sinus and orbital apex aspergillosis. Interventions: Functional endoscopic sinus surgery was performed, and a biopsy of the lesion tissue was submitted for examination, which showed the presence of aspergillus. Outcomes: One year after surgical debridement, antifungal, and anticoagulation treatments, the patient is still asymptomatic without recurrence. Lessons: Early surgical debridement is crucial to confirm the diagnosis of cavernous sinus-orbital apex aspergillosis and prevent mortality. There is no evidence of negative effects of antibiotic and anticoagulation treatments. Despite controversy, among physicians, most opt to treat patients via anticoagulation therapy.